2023
DOI: 10.3390/molecules28104109
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Coumarins from Cnidium monnieri Fruits and Angelica dahurica Roots and Their Physiological Effect on Pine Wood Nematode (Bursaphelenchus xylophilus)

Abstract: Pine wood nematode (PWN), Bursaphelenchus xylophilus, is a major pathogen of pine wilt disease (PWD), which is a devastating disease affecting pine trees. Eco-friendly plant-derived nematicides against PWN have been considered as promising alternatives to control PWD. In this study, the ethyl acetate extracts of Cnidium monnieri fruits and Angelica dahurica roots were confirmed to have significant nematicidal activity against PWN. Through bioassay-guided fractionations, eight nematicidal coumarins against PWN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Some groups of compounds identified in the present study in both species of Arthrobotrys have been found in other isolates of this genus and are associated with several biological activities. On the one hand, coumarins obtained from other sources i.e., plants and marine plants have been reported to possess important therapeutic activities, i.e., antifungal, anti-inflammatory and antimicrobial [ 38 ] and nematocidal activity [ 39 , 40 ]. On the other hand, some compounds belonging to the group of Alkaloids are also demonstrated to possess potent nematocidal activity against gastrointestinal parasitic nematodes [ 41 ] and against phytoparasitic nematodes [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some groups of compounds identified in the present study in both species of Arthrobotrys have been found in other isolates of this genus and are associated with several biological activities. On the one hand, coumarins obtained from other sources i.e., plants and marine plants have been reported to possess important therapeutic activities, i.e., antifungal, anti-inflammatory and antimicrobial [ 38 ] and nematocidal activity [ 39 , 40 ]. On the other hand, some compounds belonging to the group of Alkaloids are also demonstrated to possess potent nematocidal activity against gastrointestinal parasitic nematodes [ 41 ] and against phytoparasitic nematodes [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pine wood nematode Bursaphelenchus xylophilus is the main pathogen of pine wilt disease (PWD), which destroys the population of these trees. MFCs (isopimpinellin, bergapten, and xanthotoxin) isolated from the roots of C. monnieri and A. dahurica, considered to be environmentally friendly plant-derived nematicides, were investigated by Feng et al [54]. A strong nematicidal effect on B. xylophilus was found, affecting reproduction, egg hatching and feeding ability.…”
Section: Nematicidal Activitymentioning
confidence: 99%
“…Bursaphelenchus xylophilus (Steiner et Buhrer) is the causal agent of PWN disease 8 and is mainly transmitted through the vector Japanese pine sawyer (JPS), Monochamus alternatus. 9 The vicious infection cycle of the disease comprises PWNs, vector insects, and pine trees (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Bursaphelenchus xylophilus (Steiner et Buhrer) is the causal agent of PWN disease and is mainly transmitted through the vector Japanese pine sawyer (JPS), Monochamus alternatus . The vicious infection cycle of the disease comprises PWNs, vector insects, and pine trees (Figure a). , Therefore, the integrated control of PWNs and vector insects must be considered to cut off the infestation cycle and achieve superior control.…”
Section: Introductionmentioning
confidence: 99%